The Meaning of Bouquets Among the Ponorogo City Society: a Symbolic Interactionism Perspective - Rosyidah, Eva; Prasetiyo, Luhur (Action Research Literate, 2025)
This study aims to examine the meaning of giving bouquets among urban communities, especially as a symbol of social status and expression of emotions using a symbolic interactionism approach. In a society that is increasingly connected with the influence of social media, giving bouquets has transformed from a mere tradition into a more complex trend. Bouquets, which were once identical to flowers as an expression of affection or someone's emotions in appreciation, now involve various other forms of gifts and function as a tool to express happiness, gratitude, and social support. This study uses a qualitative approach with participatory observation methods, in-depth interviews, and documentation to explore the meaning of giving bouquets in various social contexts, such as graduations, celebrations, and personal achievements. The results of the study show that giving bouquets is not only an expression of personal emotions, but also as a status symbol that strengthens social relationships between individuals. Thus, giving bouquets functions as a social communication tool that reflects the dynamics of changing values and social interactions in society